Remarks on the Phonological Evolution of Russian in Comparison with the Other Slavic Languages - Jakobson, Roman, 1896-1982 (Book collections on Project MUSE., 2018)
This is the first English translation of a groundbreaking 1929 work in historical phonology by the renowned linguist Roman Jakobson, considered the founder of modern structural linguistics. A revolutionary treatment of the phonological evolution of Russian in relation to other Slavic languages, the book introduced a new type of historical linguistics that focused on the systematic reasons behind phonological change. Rather than treating such changes as haphazard, Jakobson here presents a "teleological," purposeful approach to language evolution. He concludes by placing his book in the context of the exciting structural developments of the era, including Einstein's theories, Cezanne's art, and Lev Berg's nomogenesis.0Translated by Ronald F. Feldstein.